2013
DOI: 10.3762/bjoc.9.55
|View full text |Cite
|
Sign up to set email alerts
|

A one-pot catalyst-free synthesis of functionalized pyrrolo[1,2-a]quinoxaline derivatives from benzene-1,2-diamine, acetylenedicarboxylates and ethyl bromopyruvate

Abstract: SummaryThe catalyst-free multicomponent reaction of 1,2-diaminobenzene, dialkyl acetylenedicarboxylates, and ethyl bromopyruvate forms pyrrolo[1,2-a]quinoxaline derivatives in good yields. Ethylenediamine also reacts under similar conditions to produce new pyrrolo[1,2-a]pyrazine derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 27 publications
(20 reference statements)
1
19
0
Order By: Relevance
“…Quinoxaline derivatives have promising biological properties because of their privileged scaffold (13)(14)(15). Several biological effects have been reported, including anticancer (14,16,17), antimicrobial (18)(19)(20)(21)(22), antiviral (23), and anti-inflammatory and antioxidant (24,25) effects.…”
mentioning
confidence: 99%
“…Quinoxaline derivatives have promising biological properties because of their privileged scaffold (13)(14)(15). Several biological effects have been reported, including anticancer (14,16,17), antimicrobial (18)(19)(20)(21)(22), antiviral (23), and anti-inflammatory and antioxidant (24,25) effects.…”
mentioning
confidence: 99%
“…It was reported that electron-withdrawing Scheme 128 One-pot synthesis of quinazolino [1,2,3]triazolo [1,4] A nitro group at the 3-position of 1,2-diamino benzene 418 was not favorable as the desired product was not obtained even after 24 h of heating [243].…”
Section: Synthesis Of Quinoxalinesmentioning
confidence: 99%
“…In contrast, when acetylenedicarboxylates were used, they underwent the cyclization and elimination to generate quinoxalines 4.5 [Eq. (4‐2) (Scheme ).…”
Section: Nitrogen‐containing Nucleophilesmentioning
confidence: 99%